Mechanisms of cataract development in adult Atlantic salmon growers relative to dietary histidine and plant feed ingredients - Tröße, Christiane (Fish Physiology and Biochemistry, 2010)
Cataracts are defined as opacities of the eye lens and can be caused by a large number of risk factors. In aquaculture, cataracts in farmed Atlantic salmon (Salmo salar L.) represent an ethical problem and can cause economical losses. A series of studies have shown the cataract mitigating effect of dietary histidine (His) levels above the currently recommended minimum requirement in Atlantic salmon smolt and that dietary His levels are reflected in the concentrations of the His-derivative Nacetylhistidine (NAH) in the lens. However, the mechanism of lens protection by dietary His is not clear and no studies with adult Atlantic salmon growers have previously been carried out. Gene expression analysis in the lens is a powerful tool to investigate the molecular mechanisms of cataract formation in Atlantic salmon. In an initial study, the possible effects of different sampling procedures and tissue preservation methods on lens gene expression and lens RNA quality were investigated. Although there was no difference in RNA quality, tissue preservation in liquid nitrogen instead of RNAlater was recommended due to practical conditions in RNA extraction. Sampling procedures lasting up to two hours and procedures not employing anaesthetics provoked expression changes of selected antioxidant and stress-responsive genes. Thus, a quick sampling protocol not exceeding 30 minutes and the use of anaesthetics were recommended for future studies. A feeding trial was carried out to investigate the effects of different dietary His concentrations and His feeding regimes on lens and muscle imidazole concentrations and on cataract formation in adult Atlantic salmon growers. Fish in their second year in sea were fed one of three diets only differing in the His content [low His (L): 9 g/kg diet, medium His (M): 13 g/kg diet and high His (H): 17 g/kg diet] for four months (June to October). Dietary His concentrations were reflected in lens NAH and to a lesser degree in muscle anserine concentrations. Between July and September, fish ...